Design, synthesis, molecular docking study, and biological evaluation of salicylaldimine derivatives as potential histone deacetylases inhibitors (HDACi) and anticancer agents - Heba M. Hesham; Deena S. Lasheen; Khaled A. M. Abouzid (Ain Shams University, 2018)
Despite the increased success rates of histone deacetylases inhibitors (HDACi) as potent anticancer agents, many metabolic obstacles face the hydroxamic acid-based HDAC inhibitors, which inspired us to develop non-hydroxamate HDAC inhibitors. Based on the established knowledge of the SAR of the reported HDAC inhibitors and based on the knowledge that salicylaldimine moiety is an established chelating agent, a series of salicylaldimine based HDAC inhibitors were designed, synthesized and biologically evaluated. The compound 14 in the present study showed considerable HDAC inhibition and potential antiproliferative activities on NCI cell lines rendering it as a good start for optimization that introduces a new class of non-hydroxamate HDAC inhibitors as potential anticancer agents.